Punishment, politics and culture - Sarat, Austin; Ewick, Patricia (Studies in law, politics, and society, 2004)
Beginning with an overview of the history and philosophy of punishment, these articles explore penal practices in the modern state and the deeper philosophical and social aspects of retributive justice.